Menyelami Tranformasi Sosial Elit Pengurus Wahidiyah Kediri Dalam Menghadapi Arus Kontroversi - Sardjuningsih (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
Wahidiyyah, which is centered in Kediri in the form of a sholawat tariqat, faces external and internal challenges. This study focuses on the Wahidiyyah elite's understanding of external-internal conflict, organizational legalization, and the socio-political values of organizational transformation amid the controversy surrounding its movement. The study used a sociological approach with the analysis of Burger and Luckman's Social Construction theory, which found that in the externalization space, conflict is understood as part of social dynamics. In the Objectivation space, legalization is the socio-political power of Wahidiyah in the midst of the current debate on society. With the issuance of the decree from the Attorney General's Office, Wahidiyah was placed in line with other Islamic religious organizations. In the Internalization Space, Wahidiyyah's socio-political values of transformation are openness, nationalism, democracy, and inclusivity. The transformation of the institution from Tarekat to Shalawat wahidiyyah as a religious organization does not change the religious orientation of wahidiyyah nor does it change its teachings and practices. The belief and enthusiasm of the congregation remain the same, as the opening of management representatives abroad is proof that wahidiyyah is loved by the congregation.